The Role of the Gut Microbiome on the Development of Surgical Site Infections - Krezalek, Monika A.; Alverdy, John C. (Clinics in Colon and Rectal Surgery, 2023)
Despite advances in antisepsis techniques, surgical site infection remains the most common and most costly reason for hospital readmission after surgery. Wound infections are conventionally thought to be directly caused by wound contamination. However, despite strict adherence to surgical site infection prevention techniques and bundles, these infections continue to occur at high rates. The contaminant theory of surgical site infection fails to predict and explain most postoperative infections and still remains unproven. In this article we provide evidence that the process of surgical site infection development is far more complex than what can be explained by simple bacterial contamination and hosts' ability to clear the contaminating pathogen. We show a link between the intestinal microbiome and distant surgical site infections, even in the absence of intestinal barrier breach. We discuss the Trojan-horse mechanisms by which surgical wounds may become seeded by pathogens from within one's own body and the contingencies that need to be met for an infection to develop.
Keywords: surgical site infection; intestinal microbiome; Trojan-horse hypothesis; metastatic infection